“Islão negro” versus “verdadeiro Islão” - dilema ou sintoma de persistente e injustificada discriminação dos muçulmanos africanos subsarianos? - Dias, Eduardo Costa (Africana Studia, 2020)
Using the pretext of the old controversy on the heuristic kindness of the expression” Black Islam”, this article approaches the question of the identitarian fluidity of the Islam. In its essence, the argumentation developed in this article concerning the particularities of some religious practices of the African black Muslins and the often difficult relations of them with other African Muslins – the socalled Muslins of Arabic origin – is directly connected with the problems derived from multiplicity of images and understandings with which the believers of Islam are faced, independently of their geography, since a very long time: polycentrism of orientation and organization; heterogeneity of representations; polymorphism in the cultural mediations, etc.